Bottom Passing of Students at SMA Negeri 1 Binamu - Sufitriyono Sufitriyono; Irvan Irvan; Muhammad Akbar Syafruddin; Agus Sutriawan; Andi Sahrul Jahrir (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objective. This quantitative descriptive study aims to determine the volleyball bottom passing ability of Binamu State High School students. The data collection techniques used are tests and measurements. Materials and Methods. The population in this study were students at SMA Negeri 1 Binamu, with a sample size of 22 students. The instrument used in this research was a test, namely the Brumbach forearm pass wall-volley test. The data analysis technique used is a descriptive percentage. Results. The research data shows that the maximum score that students can achieve is 39, and the minimum score is 24. The research data that has been classified shows that the ability to pass under volleyball in PJOK Learning at SMA Negeri 1 Binamu is in the "inferior" category at 13.6 % (3 students), the "poor" category was 18.2% (4 students), the "Enough" category was 36.4% (8 students), the "good" category was 22.7% (5 students), and the "very good" was 9.1% (2 students). Conclusion. Thus, it can be concluded that the ability to pass under volleyball in PJOK Learning at SMA Negeri 1 Binamu is in the Sufficient category.